Analysis of Supporting and Inhibiting Factors for Smoking Cessation Among The Totok Rokok Patients in Padang Panjang City - Novnariza, Elsi; Hidayat, Ahmad; Chalida Nur, Nadia; Irfa Zadzkia, Shelsa; Andri Yani, Gita; Pradipta, Yudi (Jurnal Kesehatan Saintika Meditory, 2023)
Smoking is one of preventable non-communicable diseases (NCDs) risk factors. Indonesia as the third largest number of smokers country in the world have the percentage of smokers (aged 15+ years) around 32% in 2018. The Padang Panjang City Government have commitment to solve the problem by issued a Regional Regulation regarding Smoke-Free Areas and Cigarette Order Areas No. 8 of 2009. The Padang Panjang City Government also provided ‘totok rokok’ service that available in all public health centers. This program help the smokers to improve their intention to quit smoking until succeed, but many patients also have failed or drop out. We conducted qualitative study with in-depth interview in five public health centers in Padang Panjang City. Participants in this study consist of patients of Totok Rokok Program in public health centers. Data were analyzed by triangulation. There were several factors that influence a smoker to quit smoking. The belief of patient’s susceptibility to have severe disease due to smoking, the belief that smoking can cause comorbidities which will eventually end in death, self-awareness that quit smoking can affect his health and his family as well as his own economy, and lack of motivation for quit smoking. The obstacles in achieving the goal of smokers to stop smoking such as self-inconsistent factors in undergoing therapy and environmental factors such as smoker friends that make patients failed after program.  Self factors that indicates a lack of self-motivation in decision to quit smoking, also smoker friends contributing in inconsistency of totok rokok program’s outcome. It is necessary to strengthening monitoring during and after totok rokok program in order to maintain patient’s motivation and control the smoking temptation from theirself and other smoker friends.Keywords : Totok Rokok ; Smoking; Cessation; Program